(untitled) (Global Journal of Human-Social Science, 2014)
The present study is an attempt to decompose the changes in output growth in India since 1983-84. For analysis purpose, study has bifurcated the whole period into two parts i.e. pre (1983-84 to 1993-94) and post (1993-94 to 2006-07) reforms period. Input-Output tables for the year 1983-84, 1993-94 and 2006-07 have been utilized for this purpose. Due to non-availability of recent Input-Output table, the analysis of the recent years (2007-08 to 2012-13) has been done using the data from different Economic Surveys provided by the Ministry of Finance, Government of India. The study utilized structural decomposition analysis to categorize the different sources of output growth.